Production and scientific collaboration in Organization and Representation of Knowledge: a bibliometric analysis of GT2 of ENANCIB in the period from 2009 to 2014 - Dal' Evedove Tartarotti, Roberta Cristina [UNESP]; Lopes Fujita, Mariangela Spotti [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2016)
This study aimed to characterize the Brazilian scientific community in Organization and Representation of Knowledge area of the Information Science, from the publication of proceedings papers in GT2 of the ENANCIB (Encontro Nacional de Pesquisa em Ciencia da Informacao) from 2009 to 2014 through production and connection bibliometric indicators. From the 215 proceedings papers were analyzed the most productive authors, gender relations among authors, type of authorship, the most productive institutions, the most studied themes and scientific collaboration networks among authors/institutions, built using Excel and UCINET softwares. The results indicate 27 researchers and 14 institutions as the most productive ones, especially in the Southeast Region of Brazil. Most of the proceedings papers were performed by female authors and in scientific collaboration, especially in intra-institutional collaboration and the largest collaborative network constituted by 37 authors. There was greater focus on technological and epistemological approaches and few proceedings papers about the cultural approach to the Organization and Knowledge Representation field as their universe.
Keywords: Organization and Representation of Knowledge; Scientific production; Bibliometric studies; Scientific collaboration; ENANCIB